Optimal Stabilization and Dynamic Programming - Fernando Lobo Pereira (2005)
In this article, we present and discuss the infi- nite horizon problem of optimal stabilization. Besides, the optimality conditions in the form of an Hamilton-Jacobi-Bellman equation, we present also a method to define a feedback control strategy.